Which is the optimal minimally invasive approach for distal pancreatectomy—robotic assisted or conventional laparoscopy? - Prieto, Mikel; Goh, Brian K. P. (Laparoscopic Surgery, 2018)
We read with interest the study by Guerrini et al. (1), entitled “Robotic versus laparoscopic distal pancreatectomy: an up-to-date meta-analysis”, published recently in BMC Surgery.